Water quality variation in the middle route of South-to-North Water Diversion Project, China - Wang, Yuanzhu; Wang, Chenglin; Zhang, Chunmei; Liang, Jiangkui; Mi, Wujuan; Song, Gaofei; Zhu, Yuxuan; Wang, Shulei; Shang, Yuming; Bi, Yonghong (Frontiers in Environmental Science, 2023)
The South-to-North Water Division Middle Route Project (MRP) is currently the longest inter-basin water diversion project in the world. It benefits a large population and its water quality has attracted much attention. In this study, seasonal investigations on 11 sampling sites along the MRP were conducted from 2018 to 2019; water temperature, pH, turbidity, transparency, CODMn, dissolved oxygen, total phosphorus, phosphate, total nitrogen, ammonia, nitrate, and chlorophyll a were determined synchronously. Single leakage distance clustering analysis identified the spatio-seasonal heterogeneity of physiochemical parameters. The trophic level index (TLI) and the water quality status were assessed: TLI increased and WQI decreased from south to north; TLI and WQI had seasonal differences (p < 0.001), the best water quality was observed in autumn, and the lowest TLI was observed in winter. The trophic level was “oligotrophic to mesotrophic”; water quality status was “good.” The multiple linear stepwise regression analysis confirmed that total nitrogen (TN), Chl a, and CODMn were the driving factors in water quality. These factors were applied to build the simplified WQI model, which was confirmed as a reliable method of water quality assessment for the MRP and a fitting substitute for TLI and WQI. The results provided support for the water quality evaluation of the MRP.